Peran Penting Pendidikan Lewat Makanan Bergizi dalam Meningkatkan Kesadaran Masyarakat akan Kesehatan Tubuh dan Pikiran: Studi Literatur - Juwinner Dedy Kasingku; Boy Lumoindong (Departement of Mathematics Education, 2023)
This research is qualitative, with a literature study approach, on the important role of education through nutritious food in raising public awareness of body and mind health. The food that is prepared or served at the table should be nutritious and balanced. However, the food that is prepared or served at the table should be nutritious and balanced. Unfortunately, human diseases are created by the food we eat every day, whether we realize it or not. Interestingly, the result of this study shows that the health of the body is closely related to the food consumed. Likewise with the form of the human mindset. Therefore, it is critical to pay attention to the proper type of food, method, and time to eat in order to have a positive effect on the human body and mind. Next, the Spirit of Prophecy provides insight into the impact of nutritious food on the health of the human body and mind, with the same outcome. This research also discovered that there are risks to eating nutritious foods in excess. As a result, we must exercise caution when selecting sustenance for our bodies, as our bodies are God's temple.